Solvent-assisted in situ synthesis of cysteamine-capped silver nanoparticles. (19th December 2017) - Oliva, José M; Ríos de la Rosa, Julio M; Sayagués, María J; Sánchez-Alcázar, José A; Merkling, Patrick J; Zaderenko, Ana P
Abstract: Silver nanoparticles offer a huge potential for biomedical applications owing to their exceptional properties and small size. Specifically, cysteamine-capped silver nanoparticles could form the basis for new anticancer therapies combining the cytotoxic effect of the silver core with the inherent antitumor activity of cysteamine, which inhibit cancer cell proliferation and suppress invasion and metastasis. In addition, the capability of the cysteamine coating monolayer to couple a variety of active principles and targeting (bio)molecules of interest proves key to the tailoring of this platform in order to exploit the pathophysiology of specific tumor types. Nevertheless, the chain length and conformational flexibility of cysteamine, together with its ability to attach to the surface of silver nanoparticles via both the thiol and the amine group, have made the in situ synthesis of these particles an especially challenging task. Herein we report a solvent-assisted in situ synthesis method that solves this problem. The obtained nanoparticles have been fully characterized by UV–visible absorption spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, electron diffraction measurement, high resolution transmission electron microscopy, scanning transmission electron microscopy, energy dispersive x-ray spectroscopy nanoanalysis, and dynamic light scattering measurement. Our synthesis method achieves extremely high yield and surface coating ratio, and colloidal stability over a wide range of pH values including physiological pH. Additionally, we have demonstrated that cysteamine-capped nanoparticles obtained by this method can be conjugated to an antibody for active targeting of the epidermal growth factor receptor, which plays an important role in the pathogenesis and progression of a wide variety of tumors, and induce cell death in human squamous carcinoma cells. We believe this method can be readily extended to combinations of noble metals and longer chain primary, secondary, ternary or even quaternary aminethiols.